The structure distribution in a mixed Poisson process. (1996) - Teugels, Jozef L.; Vynckier, Petra
Abstract : We use a variety of real inversion formulas to derive the structure distribution in a mixed Poisson process. These approaches should prove to be useful in applications, e.g., in insurance where such processes are very popular. This article is dedicated to the memory of Roland L. Dobrushin.